BAHASA INGGRIS - SARI, NURMALA; H, Herman; Niswaty, Risma (Universitas Negeri Makassar, 2024)
This study aims to determine and describe the process of implementing the Direct Cash Assistance Program Policy in Salutambung Village, Ulumanda District, Majene Regency. The results of the study can be concluded that the Implementation of the Direct Cash Assistance Program in Salutambung Village, Ulumanda District, Majene Regency using the theory of Charles O. Jones, (1994) has been implemented well, which is from indicator (1). organization, seen from the BLT distribution process in Salutambung Village has been running well. Sub-district assistants work together with village officials, including hamlet heads and other village officials, to determine the BLT distribution schedule. Every time there is information related to the distribution of BLT, the village is immediately notified, and the hamlet head is tasked with conveying this information to the community. The direct involvement of village officials in this process ensures the smoothness and transparency of the distribution of assistance, so that entitled people can receive BLT according to the predetermined schedule, where the flow and data collection mechanism have been carried out in accordance with applicable provisions. (2) Interpretation, regarding the level of understanding of officers in carrying out the task of distributing BLT in Salutambung Village, it is good and is carried out according to the existing technical guidelines, however, even though the policy is implemented correctly, the problem of communication and socialization to the community still needs to be improved so that all parties understand the process better. (3) Implementation, the implementation of public policy regarding the distribution of Direct Cash Assistance (BLT) in Salutambung Village, shows that the implementation of the policy has been carried out well where village officials and sub-district assistants have worked together from the data verification process to the distribution of assistance has been carried out according to the existing technical guidelines, this is an important factor in determining the effectiveness of the program. Policy implementation involves adjustments to program objectives and resources, as well as the implementation of policies that are expected to get a positive response from the community. As for Supporting Factors, the existence of the BLT program shows the government's commitment to easing the burden on affected communities, especially those who have lost their jobs or experienced a decrease in income, thereby helping to meet daily needs and strengthen the economic resilience of low-income communities, while the inhibiting factors are the lack of socialization and limited quotas for aid recipients. Keywords: Implementation, Policy, BLT Program